Pengaruh Label Halal, Harga, dan Citra Merek terhadap Keputusan Pembelian Konsumen pada Starbucks - M. Fahrul Rozjiqin; Ahmad Ajib Ridlwan (Journal of Economics and Business Aseanomics (JEBA), 2022)
The objective of this study was to identify the effect of halal labels, prices, and brand image on consumer purchasing decisions for Starbucks products to students in the city of Surabaya. The research method used is quantitative research with multiple linear regression analysis techniques. The sampling technique in this study used purposive sampling by distributing questionnaires according to predetermined respondent criteria. The results of the study stated that the halal label and brand image had a positive effect on consumer purchasing decisions. However, price has a negative effect on consumer purchasing decisions. These results indicate that students in the city of Surabaya make aspects of halal labels and brand image as determinants of consumer purchasing decisions in buying and consuming Starbucks products. While the price aspect is not part of the determinants of consumer purchasing decisions.